Bond behavior between recycled aggregate concrete and steel rebar subjected to biaxial lateral pressure. (July 2022) - Yang, Haifeng; Huang, Youdong; Lv, Liangsheng
Abstract: Eighty-four pull-out tests were carried out to study the bond behavior between recycled aggregate concrete (RAC) and steel rebar, considering different levels of recycled coarse aggregate (RA) substitution and biaxial lateral pressure. The effects of these two parameters on bond strength and peak slip were analyzed, the bond-slip constitutive relation between RAC and steel rebar under biaxial lateral pressure was established, and the energy of bonded interface was also analyzed. The results show that the failure patterns of specimens without lateral pressure were splitting failure, while the failure patterns of specimens with different biaxial lateral pressure can be classified as splitting-pull out failure. With an increase of lateral pressure, the relative bond strength, peak slip and bond energy gradually increased, whereas the relationship between RA replacement percentages and these parameters could not be clearly observed. In addition, the relative bond strength and peak slip approximately increased linearly with the increase of lateral pressure. Finally, based on the experimental results, a modified expression for bond-slip prediction was developed, taking into account damage, and the obtained results show that the predicted curves fit well with test data.